Pengaruh Efektivitas Ekstrakulikuler Koperasi, Pendidikan Kewirausahaan, dan Self-Efficacy Sebagai Variable Intervening Terhadap Intensitas Berwirausaha Pada Siswa Kelas XI IPS SMA Negeri 8 Malang - Mawaddah, Naili Ifrozul; Prayitno, Putra Hilmi; Wahjoedi, Wahjoedi; Inayati, Ro'ufah (Universitas Hamzanwadi, 2023)
This study aims to examine and analyze the effect of entrepreneurial education and cooperative extracurriculars on the entrepreneurial intensity of SMA Negeri 8 Malang students mediated by self-efficacy. The method in this study uses a quantitative approach by collecting data which is disseminated through the Google Form. The population in this study used social studies class XI students at SMA Negeri 8 Malang, and the sample for this study used a population sample technique where the sample was taken from a total population of 71 respondents. The data analysis method uses SmartPls 3.0. and SPSS. The results of research on students at SMA Negeri 8 Malang mediated by self-efficacy have succeeded in increasing the intensity of entrepreneurship in students because students are aware of the importance of entrepreneurship education from an early age.